Thermo-mechanical reliability analysis of solder joints in surface mounted printed circuit board assemblies - Ang, Kar Hwee (2008)
As the electronic packaging trend moves more toward finer pitch surface mount technology, solder joints play an even more important and crucial role in the reliability of these packages. Accelerated thermal cycling (ATC) and thermal shock (TS) test are the most common stress tests that have been used in assessing the reliability performance of solder joints in electronic assemblies. However, in package design and optimization, fatigue analysis derived by such experiments, is expensive and time consuming. Generally, based on the mean time to failure or MTTF, an ATC test would take about few months to completion. Therefore it is very important to find an alternative test method which both quantifies the solder joint reliability and yet shorten the design and verification process time preferably to a matter of days.